Effect of ADSCs on Th17/Treg and T-bet/GATA-3 in model mice with primary immune thrombocytopenia: ADSCs impact on immune balance in thrombocytopenic mice - Dong, Haijiao; Ren, Zhaoqi; Shao, Wen; Duan, Guanghua; Du, Aicui; Du, Bin (Cellular and Molecular Biology, 2024)
We aimed to observe the effects of adipose-derived mesenchymal stem cells (ADSCs) on T helper 17 (Th17)/regulatory T cells (Treg) and T-box transcription factor (T-bet)/GATA-binding protein 3 (GATA-3) in model mice with primary immune thrombocytopenia (ITP). 32 BALB/C mice were selected. ADSCs were isolated from 2 mice and cultured. The other 30 mice were randomly divided into the normal control group, the ITP model control group, and the ITP experimental group. Platelet count (PLT), Th17/Treg cells, related serum cytokines [interleukin-6 (IL-6), IL-17A, IL-10, and transforming growth factor β1 (TGF-β1)], T-bet and GATA-3 mRNA levels in peripheral blood mononuclear cells (PBMCs) in the 3 groups were detected. PLT and Treg in the ITP experimental group were significantly lower than those in the normal control group (P<0.05), but significantly higher than those in the ITP model control group (P<0.05). Th17 and Th17/Treg in the ITP experimental group were significantly higher than those in the normal control group (P<0.05), but significantly lower than those in the ITP model control group (P<0.05). Serum IL-6 and IL-17A levels, and T-bet mRNA levels in the ITP experimental group were significantly higher than those in the normal control group (P<0.05), but significantly lower than those in the ITP model control group (P<0.05). Serum IL-10 and TGF-β levels, and GATA-3 mRNA levels in the ITP experimental group were significantly lower than those in the normal control group (P<0.05), but significantly higher than those in the ITP model control group (P<0.05). ADSCs can effectively regulate Th17/Treg balance and improve T-bet/GATA-3 mRNA expression levels in ITP model mice.